Diplomasi Budaya sebagai Identitas Nasional Melalui Rumah Budaya Indonesia di Turki - Az-zahra, Kamilia Putri; Rifai, Maulana; Gustianti, Nurbani Adine (Jurnal Ilmiah Wahana Pendidikan, 2025)
Diplomacy is one way to achieve the national interests of a country. In diplomacy, culture becomes an important factor in identifying the identity of a country. Cultural diplomacy can shape a country's image in such a way as to increase state confidence in the country's performance and capabilities, which then influence national interests in various fields. Researchers used a qualitative descriptive research type in this study because it was seen as the most appropriate to explain the phenomenon to be studied, by collecting data using the literature study method. The results of this study state that the Indonesian Cultural House is considered an important factor in building diplomatic relations through cultural diplomacy to characterize Indonesia's national identity in the eyes of the international community. Build better relations between Indonesia and other countries. Through this cultural house, the spread of Indonesian cultural values is more easily accessible to the international community. Especially in cooperation with Turkey, through good relations, the Indonesian Cultural House can also be established in Turkey to introduce Indonesian culture to the Turkish people.